Antimicrobial resistance pattern and bacterial profile from ear cultures - Mehwish Sajjad Mehmood; Wajiha Iffat; Zona Irfan; Ali Hasnain Taqi; Kapil Dev Bhojwani; Shahzaib Ahmed.; Ambreen fatima (Liaquat Medical Research Journal)
Ear infections cause hearing loss, which is a hallmark of many diseases. Ear infections are more common in children than in adults. This study was conducted to isolate different pathogens from ear culture and to evaluate the antibiotic susceptibility pattern of these organisms. This was a retrospective study conducted in Diagnostic and Research Laboratory, Dow University of Health Sciences, Karachi, Pakistan. All case histories including respiratory culture and antibiotic susceptibility results were analyzed.  Culture and antibiotic susceptibility reports of patient were retrieved from record files of the department from 1st January 2021 to 31st December 2021. A total of 691 ear pus samples were identified, most frequent bacterial isolate was Pseudomonas aeruginosa (n=249, 36%) followed by Staphylococcus aureus (n=140, 20%), CONS (n= 77, 11%) and Proteus mirabilis (n=58, 8%). Penicillin had 100% and 98% resistance against Staphylococcus aureus and Coagulase negative staphylococcus, respectively, while there was 100% susceptibility against vancomycin. Colistin has 100% susceptibility against gram negative rods in our study. Growing bacterial resistance is of great concern as it alters the clinical prognosis of ear infection. Further-more this study help in choosing the correct empirical therapy for ear infections.